Investing in Youth in the MENA Region : How to Operationalize Youth Interventions (II) - Cava, Gloria La; Morgandi, Matteo; Kaur, Iqbal; Semlali, Amina (World Bank, Washington, DC, 2012)
The objective of this Fast Brief, presented in two parts, is to illustrate several concrete examples from Middle East and North Africa (MENA), Europe and Central Asia (ECA) and Latin America and Caribbean (LAC) of youth-focused Analytical and Advisory Activities (AAA), investment lending, and grant-funded engagements, which can inform the growing work program in the region. Despite all the efforts to promote growth and significant investments in education by Arab countries, a large segment of Arab youth continues to remain outside of the mainstream of economic and social life. In 2006, the MENA already exhibited the highest youth unemployment rate in the World (24.6 percent and 25.7 percent respectively) as well as the largest gender gap in unemployment. Recent estimates predict that as a result of the economic crisis, youth unemployment could increase by a further 4.6 percent in the Middle East and up to 4 percent in North Africa over the 2008-2009 periods, and impact particularly on young women.